Exploring the complex role of the Eph/Ephrin signaling in oral and maxillofacial cancers - de Lima-Souza, Reydson Alcides; Gonçalves, Moisés Willian Aparecido; Sales de Sá, Raisa; Lavareze, Luccas; Scarini, João Figueira; Kimura, Talita de Carvalho; Ribeiro, Fernanda Cristina Poscai; Altemani, Albina; Mariano, Fernanda Viviane; Fillmore, Gary Chris; Egal, Erika Said Abu (Frontiers in Oncology, 2025)
The Eph (erythropoietin-producing hepatocellular carcinoma) receptor family represents the largest subgroup within the tyrosine kinase receptor family and is recognized for its critical role in regulating the growth, migration, and survival of both normal and malignant cells. The Eph/ephrin signaling has an ambiguous role in squamous cell carcinomas of the oral region, playing both a suppressive and oncogenic role. In salivary gland cancers, the results are reserved, although they suggest that some molecules are associated with a worse prognosis for patients. This review offers a comprehensive summary of the existing literature, underscoring the evidence that supports the involvement of the Eph/ephrin signaling in oral and maxillofacial cancers. Additionally, we examine molecular discoveries that may present promising therapeutic targets for these malignancies.